2018
DOI: 10.1007/s00421-018-3845-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-volume high-intensity interval training in a community setting: a pilot study

Abstract: The present study indicates that low-volume HIIT can be feasibly implemented in a community-based setting. Moreover, our data suggest that practical (non-all-out) HIIT that requires as little as 30 min/week, either performed as 2 × 4-HIIT or 5 × 1-HIIT, may induce significant improvements in VO and cardiometabolic risk markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 51 publications
2
50
5
2
Order By: Relevance
“…The total time effort per intervention averaged 799 ± 582 minutes (range = 4‐2928 minutes). The majority of interventions used either cycling (stationary cycle ergometers or indoor spinning bikes, n = 40) or running/walking (treadmill, outdoor trails, or stair climbing, n = 25) as exercise type. One intervention applied an all‐extremity air‐braked ergometer for synchronous arm‐leg exercise, and one study implemented high‐intensity swim training .…”
Section: Resultsmentioning
confidence: 99%
“…The total time effort per intervention averaged 799 ± 582 minutes (range = 4‐2928 minutes). The majority of interventions used either cycling (stationary cycle ergometers or indoor spinning bikes, n = 40) or running/walking (treadmill, outdoor trails, or stair climbing, n = 25) as exercise type. One intervention applied an all‐extremity air‐braked ergometer for synchronous arm‐leg exercise, and one study implemented high‐intensity swim training .…”
Section: Resultsmentioning
confidence: 99%
“…195 A low volume high intensity interval training program has been shown to improve cardiorespiratory fitness and to assist in reducing the risk of cardiometabolic diseases. 196 A 4 week supplementation of 150 mg/d resveratrol was, however, not found to augment the magnitude of anaerobic exercise capacity in human subjects, or to lower the expression of PGC-1α, SIRT1, and SOD-2 genes in skeletal muscles as compared with the placebo group. 197 Similarly, no significant differences in aerobic capacity or exercise duration were observed in healthy sedentary adults following 4 weeks of 1000-2000 mg/d resveratrol supplementation, although a significant increase in hepatic enzymes, triglycerides, and total cholesterol was observed.…”
Section: Other Diseasesmentioning
confidence: 88%
“…A low volume high intensity interval training program has been shown to improve cardiorespiratory fitness and to assist in reducing the risk of cardiometabolic diseases . A 4 week supplementation of 150 mg/d resveratrol was, however, not found to augment the magnitude of anaerobic exercise capacity in human subjects, or to lower the expression of PGC‐1α, SIRT1, and SOD‐2 genes in skeletal muscles as compared with the placebo group .…”
Section: Completed Clinical Trialsmentioning
confidence: 96%
“…However, limited research has examined adherence to HIIT outside of a laboratory setting. Initial research has demonstrated previously low-active individuals can perform HIIT while supervised in a fitness facility setting [6,7] or in supervised group-based exercise classes in a community park [8], but studies have failed to assess free-living, independent physical activity behaviour and have been of limited duration (10-12 weeks). It is unclear whether HIIT is a truly viable exercise option, as compared to standard care MICT, for improving CRF and cardiometabolic risk in the real-world.…”
Section: Introductionmentioning
confidence: 99%